2018
DOI: 10.1103/physreve.98.042136
|View full text |Cite
|
Sign up to set email alerts
|

Memory effects and Lévy walk dynamics in intracellular transport of cargoes

Abstract: We demonstrate the phenomenon of cumulative inertia in intracellular transport involving multiple motor proteins in human epithelial cells by measuring the empirical survival probability of cargoes on microtubules and their detachment rates. We found the longer a cargo moves along a microtubule, the less likely it detaches from it. As a result, the movement of cargoes is non-Markovian and involves a memory. We observe memory effects on the scale of up to 2 seconds. We provide a theoretical link between the mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 46 publications
(60 reference statements)
0
52
0
Order By: Relevance
“…In recent experimental studies and modeling [66,67], the authors observed that active cargo transport tends to self-organize into Lévy walks. More specifically it has been established that the biomolecule moves along a microtubule driven by motors with a global constant velocity for some random time and then detach from the microtubule and reattaches to a new microtubule moving along another direction [62].…”
Section: Anomalous Superdiffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent experimental studies and modeling [66,67], the authors observed that active cargo transport tends to self-organize into Lévy walks. More specifically it has been established that the biomolecule moves along a microtubule driven by motors with a global constant velocity for some random time and then detach from the microtubule and reattaches to a new microtubule moving along another direction [62].…”
Section: Anomalous Superdiffusionmentioning
confidence: 99%
“…Active intracellular transport can overcome this difficulty so that motion is faster and direct specific. The particles (called in this context cargo) are carried by molecular motors along the is Brownian; the purple trajectory is from a Brownian motion with drift (67) and illustrates superdiffusion; the red trajectory is from an fBm (22) (parameter h > 1/2) and illustrates superdiffusion; the cyan trajectory is from an Ornstein-Uhlenbeck process (62) and illustrates confined diffusion; the green trajectory is from an fBm (22) (h < 1/2) and illustrates anomalous diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…fundamentally important because much research has focused on inferring active and passive states of transport within living cells using position-derived quantities such as windowed MSDs, directionality and velocity 31,25 . The trajectories are then segmented and Hurst exponents measured in an effort to characterise the behaviour of different cargo when they are actively transported by motor proteins 23,7 or sub-diffusing in the cytoplasm 32 . However, conventional methods such as the MSD and TAMSD need trajectories with many time points ( ∼ 10 2 − 10 3 ) to calculate a single Hurst exponent value with high fidelity.…”
Section: Dlfnn Allows Analysis Of Trajectories With Local Stochastic mentioning
confidence: 99%
“…It is vitally important to be able to quantitatively characterise the dynamics of organelles and cellular responses to different biological conditions 4,5,6 . Classification of different non-Brownian dynamic behaviours at various time scales has been crucial to the analysis of intracellular dynamics 7,8 , protein crowding in the cell 8,9, microrheology 10,11 , entangled actin networks 12 , and the movement of lysosomes 13 and endosomes 14 . Anomalous transport is currently analysed by statistical averaging methods and this has been a barrier to understanding the nature of heterogeneous anomalous transport.…”
Section: Introductionmentioning
confidence: 99%
“…Their trajectories could be best described by a non-Gaussian superdiffusive model, Lévy walk. Compared to random Brownian motion, Lévy walks could lead to highly efficient long-range transport in complex fluid [37][38][39] . Therefore, mediated by the swarm fluid, the highly active bacteria community create a dynamically well-organized flow transport network above their own bodies, possibly providing a long-range communication avenue for the population.…”
Section: Introductionmentioning
confidence: 99%